Higher Coffee Consumption Is Associated With Reduced Cerebral Gray Matter Volume: A Mendelian Randomization Study - Zheng, Bing-Kun; Niu, Peng-Peng (Frontiers in Nutrition, 2022)
Background: Recently published two-sample Mendelian randomization studies showed genetically predicted coffee consumption may be associated with increased risk of Alzheimer’s disease and intracerebral hemorrhage but associated with a decreased risk of small vessel ischemic stroke. We aimed to investigate the effects of genetically predicted coffee consumption on magnetic resonance imaging markers of cerebral small vessel disease and brain volume using two-sample Mendelian randomization method. Methods: Twelve single nucleotide polymorphisms in up to 375,833 individuals were used as genetics instruments for cups consumed per day of coffee. Another four single nucleotide polymorphisms from an independent sample were used to perform the replication analysis. Three single nucleotide polymorphisms in up to 45,821 individuals were used as genetics instruments for high coffee consumption vs low/no coffee consumption. Results: Mendelian randomization analysis showed coffee consumption (cups/day) was inversely associated with grey matter volume (beta –0.371, 95% confidence interval –0.596 to –0.147, p 0.001). Replication analysis and multivariable analyses after adjusting for other risk factors confirmed the effect. High coffee consumption was also suggestively associated with decreased grey matter volume (beta –0.061, 95% confidence interval –0.109 to –0.013, p 0.013) compared with low/no coffee consumption. All analyses did found effect of coffee consumption on other outcomes including white matter hyperintensity volume, mean diffusivity, fractional anisotropy, brain microbleed, total brain volume, white matter volume and hippocampus volume. Conclusion: This two-sample Mendelian randomization study showed genetically predicted higher coffee consumption is causally associated with reduced grey matter volume of the brain.